Etnobotani Kopi di Desa Bambang Kecamatan Wajak Kabupaten Malang - Jauhari, Nasrul; Hakim, Luchman; Zayadi, Hasan (Jurnal SAINS ALAMI (Known Nature), 2022)
This study aims to determine the types and characterization of coffee in Bambang Village and the pattern of cultivation and utilization of coffee in Bambang Village, Malang Regency. The method used in this study is observation and semi-structured interviews. Qualitative data analysis is presented in descriptive form. There are three types of coffee that are cultivated in Bambang Village, namely Coffea canephora, Coffea liberica and Coffea arabica. There are three constituent layers in coffee agroforestry, the top layer functions as a canopy consisting of Kaliandra, Jackfruit, Waru, Avocado, Lamtoro, Petai, Coconut. The middle layer consists of coffee, papaya and banana and the lower layer consists of taro, ginger and tubers. The complexity of making up coffee agroforestry is used as animal feed, firewood reserves, food sources, nutritional sources and building wood materials and the form of coffee utilization as a drink is often used as a daily dish, guest treats, arts, celebrations and traditional rituals.Keywords: Ethnobotany, Types of Coffee, Coffee AgroforestryABSTRAKPenelitian ini bertujuan untuk mengetahui jenis karakteristik kopi lokal dan pola budidaya serta pemanfaatan kopi yang ada di Desa Bambang Kabupaten Malang. Metode yang digunakan dalam penelitian ini adalah observasi dan wawancara semi terstruktur. Analisis data kualitatif disajikan dalam bentuk deskriptif. Terdapat tiga jenis kopi yang dibudidayakan di Desa Bambang yaitu jenis Coffea canephora, Coffea liberica dan Coffea arabica. Ada tiga lapisan penyusun di dalam agroforestri kopi Desa Bambang, lapisan atas berfungsi sebagai kanopi terdiri dari Kaliandra, Nangka, Waru, Alpukat, Lamtoro, Petai, Kelapa. Lapisan tengah terdiri dari Kopi, Pepaya dan Pisang dan lapisan bawah terdiri dari Talas, Jahe dan Umbi-umbian. Kompleksitas penyusun agroforestri kopi dimanfaatkan sebagai pakan ternak, cadangan kayu bakar, sumber makanan, sumber nutrisi dan bahan kayu bangunan dan bentuk pemanfaatan kopi sebagai minuman sering digunakan sebagaiÂ  sajian harian, suguhan tamu, kesenian, selamatan dan ritual adat.Kata kunci : Etnobotani, Jenis-Jenis Kopi, Agroforestri Kopi